STUDENT’S INITIAL ABILITY PROFILE IN DIFFERENTIATION LEARNING AT ELEMENTARY SCHOOL - Liga Puspita Sari; Ari Metalin Ika Puspita; Raden Roro Nanik Setyowati (Universitas Majalengka, 2025)
This study aims to identify the initial ability profile of 3rd-grade learners at UPT SD Negeri 18 Gresik, focusing on Pancasila literacy and cognitive skills. Data were collected through diagnostic tests, classroom observations, and student questionnaires. Results showed that 51.9% of students had moderate comprehension, while 25.9% demonstrated low understanding. Observations on October 14th, 21st, and 23rd, 2024, revealed that only 18.5% of students actively participated and showed critical thinking skills, whereas the majority still needed guidance. Questionnaire responses indicated that 44% of students felt confident, yet still required instructional support. These findings highlight the need for tailored learning strategies through differentiated instruction to address the diverse initial abilities of students. This research thus provides a solid foundation for developing differentiated LKPD to enhance students' understanding and application of Pancasila values.